Habitat‐adapted microbial communities mediate Sphagnum peatmoss resilience to warming. Issue 6 (28th March 2022) - Carrell, Alyssa A.; Lawrence, Travis J.; Cabugao, Kristine Grace M.; Carper, Dana L.; Pelletier, Dale A.; Lee, Jun Hyung; Jawdy, Sara S.; Grimwood, Jane; Schmutz, Jeremy; Hanson, Paul J.; Shaw, A. Jonathan; Weston, David J.
Summary: Sphagnum peatmosses are fundamental members of peatland ecosystems, where they contribute to the uptake and long‐term storage of atmospheric carbon. Warming threatens Sphagnum mosses and is known to alter the composition of their associated microbiome. Here, we use a microbiome transfer approach to test if microbiome thermal origin influences host plant thermotolerance. We leveraged an experimental whole‐ecosystem warming study to collect field‐grown Sphagnum, mechanically separate the associated microbiome and then transfer onto germ‐free laboratory Sphagnum for temperature experiments. Host and microbiome dynamics were assessed with growth analysis, Chl a fluorescence imaging, metagenomics, metatranscriptomics and 16S rDNA profiling. Microbiomes originating from warming field conditions imparted enhanced thermotolerance and growth recovery at elevated temperatures. Metagenome and metatranscriptome analyses revealed that warming altered microbial community structure in a manner that induced the plant heat shock response, especially the HSP70 family and jasmonic acid production. The heat shock response was induced even without warming treatment in the laboratory, suggesting that the warm‐microbiome isolated from the field provided the host plant with thermal preconditioning. Our results demonstrate that microbes, which respond rapidly to temperature alterations, can play key roles in host plant growth response to rapidly changing environments.